The Effectiveness of Nutrition Education and Utilization of Local Food Tokens in Reducing the Risk of CED and Anemia in Pregnant Women in Central Lombok - Iswari Pauzi; Ni Putu Karunia Ekayani; Yudha Anggit Jiwantoro (Universitas Pendidikan Mandalika, 2025)
This study aimed to evaluate whether nutrition education combined with the use of a local food product, TOKEN (Tongkol–Kentang/Tuna-Potato), could improve maternal nutritional indicators and reduce the risk of chronic energy deficiency (CED) and anemia among pregnant women in Jelantik Village, Central Lombok, Indonesia. A quasi-experimental one-group pretest–posttest design was conducted under the supervision of the local community health center, from April to September. Fifteen pregnant women were recruited through consecutive sampling based on eligibility criteria (willingness to participate, no severe chronic disease affecting dietary intake, and ability to attend sessions). The intervention consisted of (1) nutrition education on CED and anemia prevention, and (2) hands-on training to prepare TOKEN nuggets with standardized hygienic procedures, followed by light mentoring to encourage regular consumption and home practice. Outcomes were measured at baseline and post-intervention, including nutrition knowledge (structured questionnaire), mid-upper arm circumference (MUAC/LILA) (standard MUAC tape), and hemoglobin (Hb) levels (point-of-care testing). Pre–post changes were analyzed using paired t-test or Wilcoxon signed-rank test (p < 0.05). Results showed significant improvements in nutrition knowledge, MUAC (+0.61 cm, p < 0.001), and Hb (+0.92 g/dL, p < 0.001), with fewer women at risk of CED and anemia. Participants also improved TOKEN processing skills, supporting the feasibility of using local food. This approach may be a feasible community-based strategy to reduce CED and anemia risk, though larger studies with control groups are needed.